Effects of gasification atmosphere and temperature on char structural evolution during the gasification of Collie sub-bituminous coal - Li, Tingting; Zhang, Lei; Dong, Li; Li, Chun-Zhu (Elsevier Ltd, 2014)
Char structure is one of the important factors influencing the char reactivity during gasification. The purpose of this study is to investigate the effects of gasification atmosphere and temperature on the changes of char structure during gasification. In this study, a Collie sub-bituminous coal from Western Australia was gasified in a fluidised-bed/fixed-bed reactor at 800–900 C in three gasification atmospheres: pure CO2, 15% H2O balanced with Ar and 15% H2O balanced with CO2. The structural features of the chars produced from the gasification of Collie sub-bituminous coal at varying levels of gasification conversion were characterised with FT-Raman spectroscopy. The recorded Raman spectra between 800 and 1800 cm1 were deconvoluted into 10 Gaussian bands in order to obtain quantitative information about the key structural features of these chars. The total Raman area and the band area ratio of small and large aromatic ring systems are two important indices to study evolution of char structure during gasification. It is shown that the char structure changes drastically during gasification. The reaction pathways for char-CO2 reaction and char-H2O reaction are different. CO2 and H2O compete for active sites most likely on the char surface. For the same gasification atmospheres, the reaction pathway does not change withthe gasification temperature between 800 and 900 C.